Using Digital Marketing as a Business Development Means to Increase Sales of Veraflower MSME Products - Pusporini; Pinem, Dahlia; Yetty, Fitri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study's objective is to provide evidence for efforts to develop the Handy Craft business as one of the leading regional products. This development includes the design and implementation of Digital Marketing as a means of business development in increasing sales of Vera Flower MSME products. This study used descriptive qualitative method. A type of primary data that is a direct response to the informant. Data collection techniques based on interview, observation and documentation methods. The final result of the overall research activities it can be concluded that Vera Flower's Handy Craft Business can develop sales through digital marketing social media, the social media used are Instagram, Facebook, Whatsapp and orders can be through applications such as Shopee, Tokopedia and Lazada. Vera Flower's marketing strategy uses digital marketing strategies. The application of digital marketing carried out by Vera Flower can increase sales because consumers are reached more widely and can check the quality and reputation of products by merivew each product. And can make transactions online to facilitate clients' payment processes . Vera Flower has collaborated with the Indonesian Muslim Women Entrepreneurs Association PC Bojongsari Depok City to create and utilize Digital Marketing in marketing products